y=2/3(-3)-4

Simple and best practice solution for y=2/3(-3)-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y=2/3(-3)-4 equation:


y in (-oo:+oo)

y = -3*(2/3)-4 // + -3*(2/3)-4

y-(-3*(2/3))+4 = 0

y+2+4 = 0

y+6 = 0 // - 6

y = -6

y = -6

See similar equations:

| 7x-8y=10 | | 2y+4-4y=y+16 | | -3p^2+11p+20=0 | | 36=18*6+b | | -2y+4-4y=y+16 | | 0=-3/7x-3 | | 4/9r=12 | | -1-5x=14x-14 | | 12=-.9a | | 36=44/9*6+b | | y/7+10.1=-1.1 | | 3/4y=33 | | 5x+13=-127-9 | | 3/4y=34 | | z^2+26z+169=0 | | 6y-2-4y=-30 | | 2x+3-6=14 | | -42=6(y+12) | | 42=3*5+b | | 17=9+4a | | 7x+4=-x-84 | | 7x-9=47-7x | | x-7=-13+13x | | x+2=x-1/4 | | 10(g-5)=-80 | | 175000.00+550.00x=300440.00 | | x+3x=50 | | x+8+x=16 | | -9=-3x+x+3 | | ((32x^3)-(28x^2)-47x-12)=0 | | (-5/2x)+(3/4x)=(-3/4) | | 2(-1-1x)=-26 |

Equations solver categories